PERCUTANEOUS NEPHROLITHOTOMY THROUGH UPPER CALYCEAL APPROACH FOR COMPLEX LOWER POLAR RENAL CALCULI - Muhammad Sohail; Muhammad Akram Malik; Muhammad Khalid et al. (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: To determine the efﬁcacy of percutaneous nephrolithotomy through upper calyceal approach for removal of complex lower polar renal calculi. STUDY DESIGN: Descriptive PLACE AND DURATION OF STUDY: Departments of Urology and Renal Transplantation Allied Hospital and Madina Teaching Hospital Faisalabad, from March 2009 to February 2012. METHODOLOGY: Fifty patients having complex lower polar renal calculi were selected by nonprobability consecutive sampling. Percutaneous Nephrolithotomy (PCNL) was done by standard technique through upper calyceal approach and ﬁndings noted. Chi Square test for statistical analysis was applied. RESULT: Stone clearance was achieved in 36 (72%) patients while 14 (28%) patients had signiﬁcant residual fragments (>4mm size). In 40 (80%) patients, PCNL was done through a single percutaneous tract while in 10 (20%) patients; additional tracts were made in an attempt to clear the stones. The duration of surgery ranged from 2 – 4 hours (Mean 2.6 ± 0.64) and postoperative hospital stays varied from 2 – 9 days (Mean 3.28 ± 1.53). Haemorrhage (20%), pleural injury (10%) and both hemorrhage and pleural injury (4%) were main complications. CONCLUSIONS: PCNL through upper calyceal access for treatment of complex lower pole renal calculi offers better stone clearance with chances of increased but manageable chest complications.